Specifics of the Czech spa industry and categorization model of spa towns - Kraftová, Ivana; Mandysová, Ivana; Matěja, Zdeněk (Univerzita Pardubice, 2013)
This article provides selected information about the performance of the Czech medical spa industry, as well as the various types of stay available and their respective costs. It reveals the specific ways of how medical spa care is financed in the Czech Republic and resumes that financing methods diverge from using the public finance sources towards the private ones. In this article is developed a special model to enable easy categorization, which allows the reader to quickly ascertain fundamental information on relative attributes of spa industry. The created model is usable for marketing communication.
Keywords: Czech medical spas; funding sources; regional spa industry; categorization model